Determination of busbar system heat losses in naturally ventilated and hermetic switchgear. Issue 7 (27th March 2017) - Ryfa, Arkadiusz; Bulinski, Zbigniew; Smolka, Jacek; Bedkowski, Mateusz; Burzyński, Rafal
Abstract : The study deals with the determination of the heat losses for a switchgear busbar system. The losses were computed for both naturally ventilated and hermetic switchgear configurations. For each configuration, several levels of current were considered. The heat losses were computed in three ways. The first approach was a direct method that uses the temperatures of the busbar and the surrounding air and the heat transfer coefficient computed from the empirical correlations. In the second algorithm, an energy balance of the switchgear was performed. This approach included convective and radiative heat transfer from the casing and, in the case of ventilated switchgear, the heat removed with the air flowing through the unit. The last method was based on the data obtained from the electrical measurements of the voltage and current on the considered busbar system. An uncertainty analysis was performed to compare the accuracy of the presented approaches and to validate the quality of the solution. The results revealed good agreement between the first two approaches with respect to the electric measurement uncertainty and exhibited the deficiencies of the last one.